Chronic exposure to a 2 mT static magnetic field affects the morphology, the metabolism and the function of in vitro cultured swine granulosa cells. (December 2013) - Gioia, Luisa; Saponaro, Ilaria; Bernabò, Nicola; Tettamanti, Enzo; Mattioli, Mauro; Barboni, Barbara
<x xml:space="preserve">Abstract</x> In recent years, the exposure of organisms to static magnetic fields (SMFs) is continuously increasing. Thus, we investigated the effect of chronic exposure to a 2 mT SMF on in vitro cultured swine granulosa cells (GCs). In particular, the culture expansion (cell viability and doubling time), the cell phenotype (cell morphology and orientation, actin and α-tubulin cytoskeleton), the cell metabolism (intracellular Ca2+ concentration [Ca2+]i and mitochondrial activity) and the cell function (endocrine activity) were assessed. It has been found that the exposure to the field did not affect the cell viability, but the doubling time was significantly reduced (p < 0.05) in exposed samples after 72 h of culture. At the same time, the cell length and thickness significantly changed (p < 0.05), while the cell orientation was unaffected. Evident modifications were induced on actin and α-tubulin cytoskeleton after 3 days of exposure and, simultaneously, a change in [Ca2+]i and mitochondrial activity started to become evident. Finally, the SMF exposure of GCs longer than 72 h determined a significant alteration of progesterone and estrogen production (p < 0.05). In conclusion, our results demonstrate that the chronic exposure of swine GCs to a 2 mT SMF exerts a negative effect on cell proliferation, morphology, biochemistry and endocrine function in an in vitro model.